Analyzing Trauma and Memory as a Psychological Apparatus of Diasporic Female Identity Formation in Jhumpa Lahiri’s Roman Stories - Sanchari Chattopadhyay; Gyanabati Khuraijam (Journal of Psychosexual Health, 2026)
Introduction: Though diasporas often undergo marginalization on the basis of their ethnic difference, women in particular are often subjected to gendered trauma. It initiates post-traumatic stress disorder (PTSD), triggering a strong psychological reaction that leads to an identity crisis, and they keep on negotiating their identities based on new experiences and their encounters with the hostland inhabitants in the “sites of memory.” The article analyses female characters of Jhumpa Lahiri’s Roman Stories as models of diasporic women who shape their identity while bypassing and negotiating with the memories of the homeland or of the trauma that they had confronted. Objective: To understand how trauma functions as a psychological mechanism behind the identity formation of diasporic women and to what extent it is affected by PTSD, sites of memory, and sexuality. Method: A qualitative approach has been adopted, and textual analysis of Roman Stories has been conducted by applying theories of Pierre Nora, Gayatri Chakravorty Spivak, Cathy Caruth, Julia Kristeva, Judith Herman, and Edward Said. Ehlers and Clark’s cognitive model of PTSD has been applied to form a model of the diasporic identity formation process. Results: Diasporic subjects keep on reliving the trauma, and PTSD often leads to an identity crisis. There is a significant difference between male and female diasporic identity formation, and for females, it is often triggered by sites of memory and shaped by sexual intimacy. Identity formation is a complex process that goes from spheres of trauma to cognitive processing of trauma. Conclusion: The psychological effect of trauma in diasporic women is directly associated with acts of violence and social persecution. For a diaspora, the female body becomes a site of exotic desire, creating sexual tension, yet treating them as “other,” or sexual intimacy becomes instrumental in maintaining a connection with the memory of home. The article has analyzed the texts employing an interdisciplinary approach to combine trauma theory, memory studies, and psychology to examine the identity formation of diasporic females in relation to memory and trauma.